Pancasila Sebagai Landasan Visional bagi Spiritualitas Kehidupan Bangsa Indonesia dalam Menangani Intoleransi - Nini Adelina Tanamal; Sapta Baralaska Utama Siagian (Integritas: Jurnal Teologi, 2020)
The new order regime and the reformation era in 1998 were the events of the deterioration of the life outlook of a nation so the abolition of the policy of the dissemination ​​of the value of Pancasila and the UUD NRI 1945 Constitution of the Republic as a visual basis in social. Political and social life. Acts of radicalism and terrorism by radical groups. Psychologically the social community in a dilemmatic position has already left the old belief value, but the value of the new order is not yet available. The euphoria of freedom and reform has led to the emergence of new ideologies that are not necessarily in accordance with the values ​​of the life of the nation and state, one of which is the emergence of religious groups with radical ideologies that encourage violent acts of extremism and terrorism. Based on the description of this condition, the main problem is not yet optimal implementation of the values ​​of the Pancasila in dealing with radicalism and terrorism, thus affecting ideological resilience which ultimately impacts on national resilience. The visual foundation for Pancasila needs to be understood correctly.